Examination of postures and frequency of musculoskeletal disorders among manual workers in Calcutta, India. (2nd April 2016) - Sarkar, Krishnendu; Dev, Samrat; Das, Tamal; Chakrabarty, Sabarni; Gangopadhyay, Somnath
Abstract : Background: Manual material handling (MMH) activities require workers to adopt various awkward postures leading to the development of musculoskeletal disorders (MSD). Objectives: To investigate the postures adopted during heavy load handling and the frequency of MSDs among MMH workers in Calcutta, India. Methods: We conducted a cross-sectional study with 100 MMH workers. MSD frequency was assessed via the Standardized Nordic Questionnaire. The Ovako Working Posture Assessment System (OWAS) was used to analyze working posture. We used logistic regression to predict MSD risk factors. Results: Ninety five percent of workers reported a MSD in at least one body part in the past 12 months. According to OWAS results, 83% of the analysed work postures require immediate corrective measures for worker safety. The most harmful posture was carrying a heavy load overhead. Carrying more than 120 kg increased the odds of low back and neck pain by 4.527 and 4.555, respectively. Conclusions: This sample had a high frequency of reported MSDs, likely attributed to physiologically strenuous occupational activities repeated on average of 30–40 times daily. Ergonomic interventions, such as the use of handcarts, and occupational training are urgently needed.